PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PENDIDIKAN MULTIKULTURAL DI SMAN 9 PINRANG - Syuaib, Muhammad Mukhtar; Haddade, Hasyim; Rusmin, Muhammad (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
This research is grounded in the need for Islamic religious education that does not merely instill religious values in a dogmatic manner, but is also capable of fostering tolerant, inclusive attitudes and respect for cultural, ethnic, and religious diversity. The aim of this study is to analyze the development of Islamic Religious Education learning in the perspective of multicultural education at SMAN 9 Pinrang. This study employs a qualitative approach. Data were obtained through in-depth interviews, observation, and document analysis. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The findings indicate that the development of multicultural-based Islamic Religious Education learning at SMAN 9 Pinrang is carried out in an integrated manner through four dimensions: contextual development of learning materials, enhancement of teacher competencies in conflict resolution, cross-subject curriculum collaboration, and the involvement of parents along with continuous evaluation of students’ attitudes. This approach is systemic and comprehensive, distinguishing it from previous studies that tended to focus only on isolated aspects such as teaching methods, teacher roles, or curriculum design. These findings suggest that multicultural-based Islamic Religious Education learning can foster inclusive, dialogical, humanistic, moderate, and contextual learning practices in the dynamics of a multicultural society